The Effect Bonapace Method Reduces Labor Pain Of Active Phase I To Intranatal Care - Susiloningtyas, Luluk; Wulandari, Ratna Feti (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Sampling technique used is Accidental Sampling. The independent variable is Bonapace Method, the instrument used is a checklist. Dependent variable is the reduction of labor pain in the active phase I, an instrument used to measure the level of pre and post pain with an observation sheet with a pain scale between 0 to 10 and an interview using the Verbal Descriptive Scale (VDS), rating scale, value 0 = no pain , 1-3 = mild pain, 4-6 = moderate pain, 7-9 = severe pain, 10 = very severe pain. Analysis of data using the Wilcoxon Sign Rank. The results of the data analysis stated sig (p) = 0,000 where α = 0.05, p <α, it means that there is an effect of the Bonapace Method on the reduction of labor pain in the active phase of the First Maternity where the Correlation or effect using the Wilcoxon Correlation = -0,382